PEMBUATAN DRY BOX PENGATUR KELEMBABAN OTOMATIS SEBAGAI PENYIMPANAN KAMERA DSLR DENGAN RFID BERBASIS ARDUINO AT MEGA 2560 - Pangestu, Jaka (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2020)
Abstract. The purpose of making the tool in this study is to design, manufacture, and test the dry box of an automatic humidity control device as a camera storage with Arduino At Mega 2560 based RFID to automatically maintain camera humidity in the dry box so that mold does not appear on the camera because it will reduce the quality of the camera. is for use. This research was conducted using engineering methods with stages that include system design, subsystem identification, hardware design, software design, hardware testing, software testing, and testing analysis. The sensor used to detect the value of humidity and temperature is the DHT22 sensor. . RFID and keypad as security systems are designed with a security code and a camera reader uses a limit switch press sensor. The system created can be used to read humidity and temperature. Peltier heater is used to reduce humidity if the sensor reads the humidity exceeds 65% then the Peltier heater will turn on. The results of the reading by the system run well and also read the RFID card and security code on the system